PENGARUH MOTIVASI KERJA DAN KEDISIPLINAN TERHADAP KINERJA GURU SEKOLAH DASAR NEGERI DI KELURUHAN BINTARA KECAMATAN BEKASI BARAT - Yudha Pratama; Tatag Herbayu (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
To determine the effect of work motivation and discipline on teacher performance SDN Kelasional Bintara, West Bekasi District. Descriptive research methods, verification analysis.. Primary data types by giving questionnaires to teachers, simple linear regression analysis method and multiple. Result simultaneous work motivation and discipline have a significant effect on the performance of teachers in SDN Kelasional Bintara, West Bekasi District, while partially both work motivation and discipline have a positive and significant effect on the performance of teacher employees.